Neuvottelujärjestelmät: Tutkimustuloksia ja maiden välisiä vertailuja - Antti Kauhanen; Jenni Nevavuo (The Research Institute of the Finnish Economy (ETLA), 2021)
– This report reviews economic literature on collective bargaining systems. The studies studying the association of collective bargaining systems and employment, productivity ja wages can not establish causality and the literature is quite thin. The existing results show that coordinated systems are associated with higher employment rate, centralized systems are associated with lower productivity growth and decentralized systems are associated with higher wages. Studies do not support the claim that decentralization of collective bargaining would lead to dumping of terms of employment. Studies on wage stickiness show that wages in Finland are sticky in international comparison and that adjustment to shocks happens more through employment than wages. The bargaining systems have decentralized in Europe during the last decades. Finland has maintained its system based on coordinated sector level agreements while comparison countries moved to a more decentralized but coordinated system in the 1990s. In European comparison, Finland has high levels of trust, low levels of tension between management and employees, good participation possibilities for employees and developed social dialogue in workplaces.
Keywords: J52; J53; J38; 330; Collective bargaining; Decentralization; Local bargaining; Coordination